(3ELGRGJ GdCFeI Ydjge GdSdGes - (3CMeO Hf SYO GdOjf Hf GdMSjf Hf eMeO Hf Ydj Hf eMeO GdeShQjs
(3ChdgG (B:s
(3jbhd GdYHO CMeO Hf SYO GdOjf Hf GdMSjf Hf eMeO Hf Ydi Hf eMeO GdeShQi habg Gddg hZaQ dg (B: (3hdi ef ehdGfG CejQ GdeDefjf GdeDjO HGddg eMeO Hf Cej GdeDefjf GdbGSe Hf eMeO ELGRI YGeI eTGagI s
(3BNQgG (B:s
(3hgPg GdELGRI GdJi JdaX HgG djSJ ebUhQI Ydi HYV Ohf HYV hUdi Gddg Ydi MjQ eHYhK ef Hfi YHO efGa s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG JYdjbGJ hTQhMs
(3hgh cJGH ai WQb QhGjGJ cJH GdCFeI GdRjOjI hZjQgG ef GdcJH GdJi QhGgG CFeJge hCbQhgG (B_ (3Ke ESfGO ePgH GdRjOjI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs